A new time-domain reflectometry bridge scour sensor. (March 2013) - Yu, Xinbao; Zhang, Bin; Tao, Junliang; Yu, Xiong
Scour is a major threat to bridge safety. Bridge failures cost millions of dollars each year as the result of not only the direct costs of replacing and restoring these bridges but also the indirect costs related to the disruption of transportation network. Instruments for bridge scour monitoring are necessary to study scour process and support bridge management. Lack of robust and economic scour monitoring devices prevents the implementation of bridge scour monitoring program among bridge owners. This study describes the development of a new time-domain reflectometry scour sensor. The geometry of this sensor was designed to allow for easy installation through common geotechnical boreholes. Coating was applied to the sensor, which provided it with a large range of sensing depths compared to an uncoated metallic rod sensor. The coating also provided corrosion protection. The design of this new sensor was studied by numerical simulations with finite element method. From the results, the effective sampling areas of this sensor were determined. Laboratory evaluations showed that this sensor was sensitive to simulated scour process. An algorithm was developed to determine scour depth from sensor signals. The results indicated that the sensor provided accurate scour depth measurement.